The effect of HLA homozygosity on rubella vaccine-induced humoral and cell-mediated immune responses - Kennedy, Richard B. (2009)
Human Leukocyte Antigen (HLA) genes play a critical role in host immunity including vaccine responses. HLA molecules present antigenic peptides to T cells and provide inhibitory signals to NK cells, and polymorphisms within HLA genes allows for binding and presentation of a diverse array of self and foreign peptides. Heterozygosity across HLA alleles has been found to play a positive role in host defense for a variety of infections. Homozygosity within one or more HLA loci may restrict this epitope repertoire and limit T cell responses to infection or vaccination. Here we report that homozygosity within the HLA DPB1 locus is associated with increased levels of rubella-specific IgG, an effect driven by a common allele DPB1*0401. We also show that homozygosity within different HLA class I and class II loci is correlated with variations (but not necessarily decreases) in IL-2, IL-5, and IL-10 secretion following rubella virus stimulation.